The Relationship Between Organizational Citizenship Behaviour and Organizational Silence - Valliappan Raju, Assoc. Prof. Dr.; Md Rom Bin Tamjis, Prof Dr. (International Journal of Engineering and Technology, 2019)
This paper investigates how a parameter of authoritative quietness affects hierarchical citizenship practices. In the paper, authoritative quietness is perceived as a multidimensional factor from which the impact on hierarchical citizenship practices can be investigated. The study gains insights form 462 employees in a multinational private business firm. The research context is Istanbul. The research embraced a survey technique. From the findings, passive quietness has a negative impact on hierarchical citizenship behavior. However, pro-social quietness was found to pose a positive effect on authoritative citizenship behavior.